1 Acts of Assembly, Passed in the Colony of Virginia, From 1662 to 1715, at 147 (1727) - (:unkn) unknown (My University, 1684)
Prohibited impressing or taking from any person arms "that are already provided, or shall so provide or furnish himself; neither shall the same be liable to be taken by any Distress, Seizure, Attachment, or Execution?"?"
Keywords: EXEMPTION FROM SEIZURE